Analisis Kemampuan Literasi Matematika SIswa SMP Dalam Pemecahan Masalah Matematika Ditinjau dari Perbedaan Gender - Sisca Sulistianingtiyas; Iis Holisin; Endang Suprapti (Universitas Muhammadiyah Surabaya, 2024)
This descriptive research with a qualitative approach aims to describe the level of mathematical literacy of junior high school students in solving mathematics problems in terms of gender differences. The research subjects consisted of six students with high, medium and low categories. The data collection techniques used were tests, interviews, and documentation. Triangulation techniques were used to analyze the results of written tests and interviews. The results showed that gender has an effect on solving math problems. Male students with low ability tended to give short answers without detailed explanations, while male students with medium and high ability were able to explain the solution steps better. Female students with low ability had difficulty in writing formulas and solution steps, while female students with medium and high ability could explain and write the solution method clearly. The difference in problem solving methods between male and female students can be seen in fulfilling the indicators of mathematical literacy based on Polya. Male students were able to mention four indicators of mathematical literacy compared to female students who were able to mention three indicators of the four indicators, but female students tended to be better at communicating the explanation of the problem solving. The difference in mathematical literacy of male students is equal to that of female students, with the difference lying in the ways and stages of solving the problems given.